Tumour suppressor gene function in carcinoma‐associated fibroblasts: from tumour cells via EMT and back again?. Issue 3 (February 2014) - Drake, Lauren E; Macleod, Kay F
Abstract Recent reports indicate that inactivation of the RB, TP53 or PTEN tumour suppressor genes is detected in tumour stroma of oropharyngeal, breast and other human cancers. Mouse models have validated the tumour-promoting effects of deleting Rb, Pten or p53 in fibroblasts that converts them from normal fibroblasts to carcinoma associated fibroblasts (CAFs). The tumour-promoting activity of CAFs in these contexts was associated with increased paracrine signaling to tumour cells through production of specific growth factors, chemokines and MMPs by CAFs. The conversion of NOFs into CAFs through acquisition of specific mutations, such as loss of tumour suppressors, or deregulated expression of microRNAs or key epigenetic events, can clearly occur independently of genetic and epigenetic changes in tumour cells but an alternative source of CAFs that is being reconsidered is that CAFs derive from the tumour cells by EMT. Recent mouse models employing lineage-tracing techniques have suggested that this can take place in vivo and the extent to which this is relevant more broadly is discussed. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.